Upaya Meningkatkan Hasil Belajar Pendidikan Pancasila dan Kewarganegaraan pada Materi Pengelolaan Kekuasaan Negara melalui Model Kooperatif Tipe Make a Match di Kelas XII MIPA 2 SMA Negeri 1 Ciampea Kabupaten Bogor Tahun Pelajaran 2017/2018 - Ibnu Tricahyono (Institut Agama Islam Sahid (INAIS) Bogor, 2019)
This Classroom Action Research was conducted to solve the problem of low learning outcomes of Class XII MIPA 2 students at SMA Negeri 1 Ciampea, Bogor Regency. This can be seen from the learning outcomes of students on state power management material, namely 43% below the KKM, while the KKM is set at 70. The learning model used in this study is the make a match type cooperative learning model, which is a method used by the teacher in the process of learning by means of students matching question cards and answer cards. The results of this study indicate that the use of the make a match cooperative learning model can improve the learning outcomes of Class XII MIPA 2 students at SMA Negeri 1 Ciampea, Bogor Regency. Evidenced by the increase in learning outcomes cycle 2 to cycle 1 by 13%. The final result is that 83% of students get 70 and only 7 students score below the Minimum Completeness Criteria. The conclusion from this study is that the make a match type of cooperative learning model is proven to be able to improve student learning outcomes, it can be used in Civics learning which does not require solving difficult problems.